Mediating in intercultural communicative challenges issued in the language classroom: a new objective in training programs for new teachers - Sanchez-Sanchez, Gabriel; Krawiec, Marek (Lingua Posnaniensis, 2018)
The Faculty of Education Universidad de Murcia (Spain) offers a four-year degree programme in primary education, where modules and subjects related to the foreign language (English) are taught in the first, third and fourth years (OJE 2010). The current teacher training programmes should take into account the most recent political events in Europe so that they can be adjusted to suit the Council of Europe’s original linguistic and cultural education policy. This article will explore intrinsic aspects of foreign language and culture teaching, and the learning process, in relation to communication and understanding among all European citizens. This analysis will help to identify the implications of 21st-century education policy in terms of the skills of newly-qualified teachers.